2013
DOI: 10.4317/medoral.17863
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine alcohol base mouthrinse versus Chlorhexidine formaldehyde base mouthrinse efficacy on plaque control: Double blind, randomized clinical trials

Abstract: Background: Chlorhexidine is well known for its antiplaque effect. However, the mouthrinse based chlorhexidine antiplaque efficiency may vary according to the formulation of the final product. The aim of the present study was to compare anti-plaque effectiveness of two commercial mouthrinses: 0.12 % Chlorhexidine alcohol base (CLX-A) versus a diluted 0.1% Chlorhexidine non-alcohol base with 0.1% of Formaldehyde (CLX-F). Material and Methods: the study was a seven day randomized, double-blind, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
8
0
2
Order By: Relevance
“…In the literature, it is controversial the results of efficacy studies with mouthwashes with or without alcohol. Studies showed that the alcohol enhanced the antimicrobial effects of the chlorhexidine mouthwash , on the other hand, another study found no difference between those mouthwashes , which is in accordance with the present study. Those results support the industry approach of taking out the market of the mouthwashes with alcohol.…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, it is controversial the results of efficacy studies with mouthwashes with or without alcohol. Studies showed that the alcohol enhanced the antimicrobial effects of the chlorhexidine mouthwash , on the other hand, another study found no difference between those mouthwashes , which is in accordance with the present study. Those results support the industry approach of taking out the market of the mouthwashes with alcohol.…”
Section: Discussionsupporting
confidence: 92%
“…After the treatment, plaque indexes were recorded. The mean plaque of first group (0.76±0.38) was significantly lower compared to the second group (1.43±0.56), showing that alcohol might have some influence on the antiplaque effect of CHX [35].…”
Section: Commercial Agents and Biofilm/mentioning
confidence: 83%
“…Several were the methodologies regarding the use of rinses in every mouth disinfection therapy. Were evaluated individuals using rinses: chlorhexidine for two months (1,3,4), chlorhexidine for 2 weeks, mouthrinse with essential oils (2), without the use of any substance (19) and support antibiotics with associated (11,22). Because of the unique characteristics of chlorhexidine 0.12%, and respecting the limits on the use of the substance chose the use of protocol for seven days, and the results show similarities with other studies (1,4) when the use of chlorhexidine for two months.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine is an effective oral antiseptic agent, that has proven antimicrobial effect and when used in a rational way can be an important tool in controlling periodontal disease (11). Prolonged use of chlorhexidine may cause numerous side effects, such as the presence of stains on tooth surfaces and change in taste (12), mucosal irritation, and burning sensations in the mucosa (13).…”
Section: Introductionmentioning
confidence: 99%